Electronic properties of bulk and thin film SrRuO3: a search for the metal-insulator transition. - SANVITO, STEFANO; CAFFREY, NUALA; CAFFREY, NUALA (My University, 2008)
We calculate the properties of the 4d ferromagnet SrRuO3 in bulk and thin film form with the aim of understanding the experimentally observed metal-to-insulator transition at reduced thickness. Although the spatial extent of the 4d orbitals is quite large, many experimental results have suggested that electron-electron correlations play an important role in determining this material?s electronic structure. In order to investigate the importance of correlation, we use two approaches which go beyond the conventional local-density approximation to density-functional theory (DFT): the local spin-density approximation+Hubbard U (LSDA+U) and the pseudopotential self-interaction correction (pseudo-SIC) methods. We find that the details of the electronic structure predicted with the LSDA do not agree with the experimental spectroscopic data for bulk and thin film SrRuO3. Improvement is found by including electron-electron correlations, and we suggest that bulk orthorhombic SrRuO3 is a moderately correlated ferromagnet whose electronic structure is best described by a 0.6 eV on-site Hubbard term, or equivalently with corrections for the self-interaction error. We also perform ab initio transport calculations that confirm that SrRuO3 has a negative spin polarization at the Fermi level, due to the position of the minority Ru?4d band center. Even with static correlations included in our calculations we are unable to reproduce the experimentally observed metal-insulator transition, suggesting that the electronic behavior of SrRuO3 ultrathin films might be dominated by extrinsic factors, such as surface disorder and defects, or due to dynamic spin correlations which are not included in our theoretical methods.
PUBLISHED
Keywords: Physics; thin films; Nanoscience & Materials